Leptin Receptor Blockade Attenuates Hypertension, but Does Not Affect Ventilatory Response to Hypoxia in a Model of Polygenic Obesity - Kim, Lenise J.; Shin, Mi-Kyung; Pho, Huy; Otvos, Laszlo; Tufik, Sergio; Andersen, Monica L.; Pham, Luu V.; Polotsky, Vsevolod Y. (Frontiers in Physiology, 2021)
Background: Obesity causes hypertension and exacerbates sleep-disordered breathing (SDB). Leptin is an adipocyte-produced hormone, which increases metabolic rate, suppresses appetite, regulates control of breathing, and increases blood pressure. Obese individuals with high circulating levels of leptin are resistant to metabolic and respiratory effects of leptin, but they appear to be sensitive to hypertensive effects of this hormone. Obesity-induced hypertension has been associated with hyperleptinemia. New Zealand obese (NZO) mice, a model of polygenic obesity, have high levels of circulating leptin and hypertension, and are prone to develop SDB, similarly to human obesity. We hypothesize that systemic leptin receptor blocker Allo-aca will treat hypertension in NZO mice without any effect on body weight, food intake or breathing. Methods: Male NZO mice, 12-13 weeks of age, were treated with Allo-aca (n=6) or a control peptide Gly11 (n=8) for 8 consecutive days. Doses of 0.2 mg/kg were administered subcutaneously 2x/day, at 10 AM and 6 PM. Blood pressure was measured by telemetry for 48 hours before and during peptide infusion. Ventilation was assessed by whole-body barometric plethysmography, control of breathing was examined by assessing the hypoxic ventilatory response (HVR), and polysomnography was performed during light-phase at baseline and during treatment. Results: Systemic leptin receptor blockade with Allo-aca did not affect body weight, body temperature, and food intake in NZO mice. Plasma levels of leptin did not change after the treatment with either Allo-aca or the control peptide Gy11. NZO mice were hypertensive at baseline and leptin receptor blocker Allo-aca significantly reduced the mean arterial pressure from 134.9±3.1 mmHg to 124.9±5.7 mmHg during the light phase (P<0.05), whereas the control peptide had no effect. Leptin receptor blockade did not change the heart rate. Allo-aca did not affect minute ventilation under normoxic or hypoxic conditions and HVR. Ventilation and oxygen desaturation during NREM and REM sleep did not change with leptin receptor blockade. Conclusions: Systemic leptin receptor blockade attenuates hypertension in NZO mice, but does not exacerbate obesity and SDB. Thus, leptin receptor blockade represents a potential pharmacotherapy for obesity-associated hypertension.